Border militarization via drug and immigration enforcement: human rights implications - Dunn, Timothy J. (Social justice, 2001)
Focuses on the militarization of law enforcement on the United States-Mexico border policy in the United States. Implication of the Redford shooting incident to border militarization; Threat of human rights on militarization law enforcement; Change in border militarization after the Redford shooting incident.